2020
DOI: 10.1093/mnras/staa539
|View full text |Cite
|
Sign up to set email alerts
|

Planet gap opening across stellar masses

Abstract: Annular structures in proto-planetary discs, such as gaps and rings, are now ubiquitously found by high-resolution ALMA observations. Under the hypothesis that they are opened by planets, in this paper we investigate how the minimum planet mass needed to open a gap varies across different stellar host masses and distances from the star. The dependence on the stellar host mass is particularly interesting because, at least in principle, gap opening around low mass stars should be possible for lower mass planets,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 86 publications
2
15
0
Order By: Relevance
“…ALMA Cycle 3 observations of CIDA 1 revealed for the first time a dust-depleted inner cavity around a VLMS, with a ring with maximum brightness at ∼20 au (Pinilla et al 2018a), which is a typical feature of the transition disk (TD) population. The observed structure in CIDA 1 may suggest that cavity opening processes are common in millimeter-bright disks independent of the central star mass, including VLMSs (Pinilla et al 2018b(Pinilla et al , 2020Sinclair et al 2020).…”
Section: A122 Page 1 Of 13mentioning
confidence: 93%
“…ALMA Cycle 3 observations of CIDA 1 revealed for the first time a dust-depleted inner cavity around a VLMS, with a ring with maximum brightness at ∼20 au (Pinilla et al 2018a), which is a typical feature of the transition disk (TD) population. The observed structure in CIDA 1 may suggest that cavity opening processes are common in millimeter-bright disks independent of the central star mass, including VLMSs (Pinilla et al 2018b(Pinilla et al , 2020Sinclair et al 2020).…”
Section: A122 Page 1 Of 13mentioning
confidence: 93%
“…Pinilla et al (2018a) have thus far reported the lowest mass star with a resolved large dust cavity (radius ∼20 au) in the disk around the M 4.5 star CIDA 1. In the context of planets creating such a cavity, it has been shown that a high planet-to-stellar mass ratio is needed to open a gap and trap particles in disks around VLMS, because in these cases, the disk scale height at a given location is higher than in moderate or high mass stars (Pinilla et al 2017a;Sinclair et al 2020). In a typical disk around a VLMS as CIDA 1, at least a Saturn-mass planet is needed to open a gap in the disk.…”
Section: Introductionmentioning
confidence: 99%
“…At inner and outer boundaries, the gas velocities and densities are fixed to the initial steady-state value while the dust has an open inner boundary (Meru et al 2019;Sinclair et al 2020). We adopt the damping procedure (de Val-Borro et al 2006) to avoid artificial wave reflection.…”
Section: Numerical Setupmentioning
confidence: 99%